I have constructed a big prime field:

p=68235916425158872634653027 F=GF(p) And then I make two extension field E1=GF(p^2) E2=GF(p^6) It is obvious that E2 is the extension field of E1. Now how can I express the element in E2 with the basis in E1.

1 | initial version |

I have constructed a big prime field:

p=68235916425158872634653027 F=GF(p) And then I make two extension field E1=GF(p^2) E2=GF(p^6) It is obvious that E2 is the extension field of E1. Now how can I express the element in E2 with the basis in E1.

I have constructed a big prime field:

p=68235916425158872634653027 F=GF(p) And then I make two extension field E1=GF(p^2) E2=GF(p^6) It is obvious that E2 is the extension field of E1. Now how can I express the element in E2 with the basis in E1.

I have constructed a big prime field:

`p = 68235916425158872634653027 F = GF(p)`

~~p=68235916425158872634653027 F=GF(p)~~And then I make two extension~~field~~fields~~E1=GF(p^2) E2=GF(p^6)~~`E1 = GF(p^2) E2 = GF(p^6)`

It is obvious that

~~E2~~`E2`

is~~the~~a field extension~~field~~of~~E1.~~`E1`

. Now how can I express the element in`E2`

~~in E2~~with the basis in~~E1.~~`E1`

.

I have constructed a big prime field:

```
p = 68235916425158872634653027
F = GF(p)
```

And then I make two extension fields

```
E1 = GF(p^2)
E2 = GF(p^6)
```

It is obvious that `E2`

is a field extension of `E1`

.
Now how can I express the element in `E2`

with the basis in `E1`

.

Copyright Sage, 2010. Some rights reserved under creative commons license. Content on this site is licensed under a Creative Commons Attribution Share Alike 3.0 license.